Housing Vienna: The Socio-Spatial Effects of Inclusionary and Exclusionary Mechanisms of Housing Provision - Friesenecker, Michael (2021)
The provision of housing plays a decisive role in segregation processes. In a European context increasingly influenced by variegated neo-liberal housing policies, Vienna’s approach is characterised by generous access to social housing. This inclusive strategy aims at actively preventing segregation and the isolation of certain groups. Over the last 30 years, however, reconfigured multi-level arrangements and wider contextual changes have transformed Vienna’s housing governance. This article explores how. In particular, it aims at disentangling the relationship between housing policy reforms at multiple policy levels and the changes of the mechanisms shaping the access to tenure segments and residential segregation in Vienna. Through the use of process tracing, we identify critical junctures of housing governance and relate them to housing segmentation and segregation measures over a period of approximately 30 years. Our findings show that reforms on multiple levels produce an increasingly deregulated private rental market and an increasingly fragmented access to a diversified provision of social housing. From a spatial point of view, persistent patterns of segregation blend with new ones, leading to decreasing segregation characterised by a more even spatial distribution of low and high-status groups. At the same time, both groups show very low, but slightly increased levels of isolation. Tenant profiles in social housing are, however, generally still very mixed. Balancing the trade-off between a social mix and social targeting without excluding residents in need will remain the main challenge for Vienna’s social housing model.